Generalized Markov modeling for flat fading. - Babich, F.
This paper investigates the properties of a method for obtaining Markov models of unspecified order to be applied to narrow-band fading channels with additive white Gaussian noise. The models are obtained by applying the context tree pruning algorithm to experimental or simulated sequences. Fading environments are identified in which the extension from first-order to higher order models is justified. The paper presents, as examples, the evaluation of the covariance function and the packet error distribution
Keywords: Additive white Gaussian noise; Context tree pruning algorithm; Covariance function; First-order models; Flat fading; Generalized Markov modeling; Higher order models; Narrow-band fading channels; Packet error distribution